"Cuidado humanizado en pacientes privados de la libertad, dilemas éticos, impacto y estrategias de intervención" - Cabrera Olvera, Jorge Leodan (2025)
"Introduction: prison health care faces several challenges, such as insufficient resources, inadequate infrastructure and social stigmatization, which negatively affect the treatment of persons deprived of liberty, these factors limit prisoners' access to basic services and impair their physical and mental health in this context, humane and ethical care is essential, which requires inclusive policies and adequate professional training. Methods: a qualitative and descriptive study was conducted based on a literature review of the last five years, and 30 articles in English, Spanish and Portuguese were selected from 65 initial studies repositories such as SCOPUS, SCIELO and PUBMED were used, and keywords and Boolean operators were employed the data were analyzed using inductive methods to identify relevant trends. Results: ethical dilemmas regarding dignity and medical care in prisons were identified these problems are aggravated by factors such as overcrowding, discrimination and poor training of health professionals. The implementation of promotion, prevention and empathy training programs has shown improvements in the wellbeing of inmates, emphasizing the importance of the interdisciplinary approach and the strengthening of family relationships. Conclusions: humane care is essential to meet the needs of all inmates and ensure that they are treated with dignity. Creating a more just and humane prison system requires inclusive public policies, ongoing staff training and educational programs that promote social reintegration."